A series of water-soluble photosensitizers based on 3-cinnamoylcoumarin for in vitro antimicrobial photodynamic inactivation. Issue 31 (9th May 2018) - Sun, Zhiyuan; Zhou, Shaona; Qiu, Haixia; Gu, Ying; Zhao, Yuxia
Abstract : Three cationic PSs (M3–M5 ) exhibited equivalent photodynamic inactivation (PDI) efficacies to MRSA and A. baumannii, whileM4 andM5 showed significantly higher PDI to C. albicans, compared to methylene blue, indicating their large potentials on PDI. Abstract : A series of novel water-soluble photosensitizers (PSs;M1–M5 ) based on 3-cinnamoylcoumarin derivatives, incorporating carboxylic acid salt (M1, M2 ), pyridine salt (M3, M4 ) and quaternary ammonium salt (M5 ) groups, were designed and synthesized. Their photophysical and photochemical properties and in vitro antimicrobial photodynamic inactivation (PDI) were investigated.M2, modified with two carboxylic acid salts, was unstable in phosphate-buffered saline (PBS). The four other PSs all showed higher binding/uptake to methicillin-resistant Staphylococcus aureus (MRSA), A. baumannii and C. albicans compared with the clinical drug methylene blue (MB ), except forM1 to A. baumannii . Furthermore, the three cationic PSs (M3–M5 ) exhibited equivalent antibacterial PDI efficacies against MRSA and A. baumannii compared withMB . The antifungal efficacies ofM4 andM5 to C. albicans were both significantly higher than that ofMB, especially forM5, indicating that the quaternary ammonium-salt-modified coumarin derivative has substantial potential for antifungal PDI.